Fenomena Dakwah Komunitas Great Muslimah Bandung - Ruli Andini, Wini (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2013)
This study examines the phenomenon of da’wah carried out by the Great Muslimah Bandung Community as a contemporary form of Islamic propagation that has emerged among urban Muslim women. The research aims to analyze the da’wah strategies encompassing the aspects of message content, methods, and media used in the community’s activities, as well as to identify the supporting and inhibiting factors influencing their implementation. Employing a qualitative descriptive approach, the study collected data through observation, interviews, and documentation involving members and organizers of the Great Muslimah Bandung Community. The findings reveal that the community’s da’wah activities emphasize spiritual strengthening, character building, and women’s empowerment through social programs, Islamic study sessions, and the utilization of digital media. The da’wah materials delivered are contextual and tailored to the needs of young Muslim women in the modern era. The methods adopted are participatory, combining educational and inspirational approaches, while the media used include social platforms such as Instagram and YouTube as tools for disseminating Islamic messages. The study concludes that the Great Muslimah Bandung Community has successfully developed a creative and adaptive model of da’wah that integrates spiritual values with the dynamics of modern life, thereby strengthening the role of women as agents of social change in the digital age.